AWARENESS ABOUT MEDICINAL USES OF COSTUS PICTUS PLANT AMONG DENTAL STUDENTS - Saivarshine,; Ganapathy, Dhanraj; Sasan, Keerthi (International Journal of Psychosocial Rehabilitation, 2020)
Costus igneus, typically known as searing costus, is native to South America and ordinarily known as the insulin plant. It is typically grown in gardens mostly as a decorative herb in South India and is further out of control in other areas. It is used in India to combat hyperglycemia and many other diseases. This survey was performed with the purpose of assessing the knowledge and the awareness about the Costus pictus medicinal plant amongst dental students. A cross-sectional survey was performed with a self-administered questionnaire with ten questions circulated among 100 dental students. The questionnaire assessed the awareness about the Costus pictus plant, their medicinal uses, antidiabetic activity, and antioxidant and antimicrobial activity. The responses were recorded and analyzed. 93% of the respondents were not aware of the medical uses of Costus pictus . 95% were not aware of the antidiabetic activity of Costus pictus . 97 % were not aware of the antioxidant activity of Costus pictus . Again, 97% were not aware of the antimicrobial activity of Costus pictus. The knowledge and awareness about the medicinal Costus plant was less among dental students, and awareness was created about its medicinal uses.